Structural Breaks, Twitter and the Stock Liquidity of Internet Dot-com Company: Evidence from US Companies - Osabuohien-Irabor, Osarumwense (The European Journal of Applied Economics, 2021)
The goal of this paper is to explore relationship between Twitter and stock liquidity of some large US internet Dot-com companies in the presence of unknown structural breaks for the period from September 2019 to April 2020. Using the Andrews-Ploberger and Andrews-Quandt structural break models, we identify the major structural breakpoints in the stock liquidity and find that most of these structural changes are significantly perceived. When we examined the sub periods as well as the full sample, Tweets and likes from most numbers of companies were found not to have links with stock liquidity. These results provide crucial insight into portfolio strategy to both international and local investors.